2020
DOI: 10.1002/sctm.19-0195
|View full text |Cite
|
Sign up to set email alerts
|

CD34+CD146+ adipose-derived stromal cells enhance engraftment of transplanted fat

Abstract: Fat grafting is a surgical technique able to reconstruct and regenerate soft tissue. The adipose-derived stromal cells (ASCs) within the stromal vascular fraction are believed to drive these beneficial effects. ASCs are increasingly recognized to be a heterogeneous group, comprised of multiple stem and progenitor subpopulations with distinct functions. We hypothesized the existence of an ASC subpopulation with enhanced angiogenic potential. Human ASCs that were CD34+CD146+, CD34+CD146−, or CD34+ unfractionated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Another study also reported a tendency for stronger adipogenic potential of cells isolated with water jet-assisted liposuction versus cells obtained by suction-assisted liposuction [12] . We have also described that CD146 + ASCs have enhanced angiogenic potential [10] , which was confirmed by another recent study that showed the benefits of supplementing fat grafts with CD146-selected cells [16] . We found that there was a tendency for higher in vitro angiogenesis evoked by water jet-isolated cells and higher secretion of VEGF-A.…”
Section: Discussionsupporting
confidence: 71%
“…Another study also reported a tendency for stronger adipogenic potential of cells isolated with water jet-assisted liposuction versus cells obtained by suction-assisted liposuction [12] . We have also described that CD146 + ASCs have enhanced angiogenic potential [10] , which was confirmed by another recent study that showed the benefits of supplementing fat grafts with CD146-selected cells [16] . We found that there was a tendency for higher in vitro angiogenesis evoked by water jet-isolated cells and higher secretion of VEGF-A.…”
Section: Discussionsupporting
confidence: 71%
“…Incubation was performed with anti‐CD31 primary antibody (1:100, ab28364; Abcam) followed by an Alexa Fluor 647‐conjugated donkey anti‐rabbit IgG secondary antibody (1:500, ab150075; Abcam). Red pixel area was obtained from 20× magnification images ( n = 15 per condition) via ImageJ (NIH) analysis that recognized red hues, binarized the images and counted selected pixels 31 …”
Section: Methodsmentioning
confidence: 99%
“…Adipose‐derived stromal cells were sorted out of the resuspended pellet from liposuction in FACS buffer and stained with antibodies for human reactivity: CD45‐Pacific blue (BioLegend, Cat#304022) to indicate hematopoietic cells; CD235a (Glycophorin A)‐eFluor 450 (BioLegend, Cat#349108) to indicate erythrocytes, and erythroid progenitors; CD31(PECAM‐1 or platelet endothelial cell adhesion molecule)‐eFluor 450 (BioLegend, Cat#303114) to indicate endothelial cells; CD34‐AlexaFluor‐488 (BioLegend, Cat#343517); and CD146‐PE/Cy7 (BioLegend, Cat#361007). To isolate the ASC subpopulations of interest, flow cytometry (FACS Aria II, BD Biosciences) was performed to create a Lineage‐negative (CD45‐CD235a‐CD31) and a positive gating strategy: CD34+CD146+, CD34+CD146−, and unfractionated (UF) CD34+ ASCs (Figure 2) (Borrelli, Patel, Blackshear, et al., 2020). Purity was tested prior ASC subpopulation sorting via analysis of a 2000 fresh cell sort that resulted in >99% purity for the three subpopulations of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we described a stromal cell subpopulation within SVF cells positive for CD34 and CD146 with increased expression of vascular endothelial growth factor (VEGF) and angiopoietin (ANGPT)‐1 (Borrelli, Patel, Blackshear, et al., 2020). These cells promoted vessel formation within human fat grafts placed into mice and ultimately increased graft retention (Borrelli, Patel, Blackshear, et al., 2020). However, this study only observed CD146+ ASCs within fat grafts in nonirradiated mice.…”
Section: Introductionmentioning
confidence: 99%